Mid-infrared Fano resonance in heavily doped silicon and metallic nanostructures due to coupling of Wood–Rayleigh anomaly and surface plasmons. (26th April 2017) - Nguyen-Huu, N; Cada, M; Ma, Y; Che, F; Pistora, J; Yasumoto, K; Ma, Y; Lin, J; Maeda, H
Abstract: This study reports the design and analysis of a plasmonic sensor based on a heavily doped silicon and metallic grating structure working in the mid-infrared region. The numerical results show that the reflection spectrum of the phosphorous-doped Si grating structure with a dopant concentration of 1 × 20 20 has a sharp asymmetric Fano resonance dip, which is strongly dependent on the refractive index change in the surroundings. It yields a sensitivity of 8000 nm/RIU (refractive index unit) and 950 nm/RIU working in the air and water media, respectively, very high values compared with that of existing devices. Moreover, the Fano resonance caused by coupling of the Wood–Rayleigh anomaly and surface plasmon resonances is demonstrated by calculating the magnetic field and Poynting vector patterns. Further, a feasible and easy fabrication process of the sensor featuring high performance is represented.